2021
DOI: 10.47948/efad.987160
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Metaphoric Perceptions of Generation Z Towards the Ideal Manager: The Case of Aksaray

Abstract: Gelişen teknolojinin içinde dünyaya gelen Z kuşağı, teknolojinin öncülük ettiği değişimi yaşamın bir parçası olarak algılamış ve hayatı da bu yönde şekillenmiştir. İnternetin yaygınlaşmasıyla birlikte bilgiye ulaşma imkânları geliştiği için kendilerini çok yönlü olarak geliştirme fırsatı bulan bu kuşak özellikle sosyal medya aracılığıyla haberleşme ve organize olma becerisine sahiptir. Literatürde yaygın olarak 2000'li yılların başında dünyaya gelen kuşak olarak kabul gören Z kuşağı iş yaşamında varlığını henü… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…It is stated that providing this atmosphere will increase their loyalty to the company and they will adapt to changing conditions more easily (Bieleń and Kubiczek, 2020). In the study conducted to reveal the ideal manager profile of Generation Z, it is suggested by young people that being like a friend, who will protect and look after them, is important for the leader to be a reliable manager (Aydoğdu and Kara Özkan, 2021). Our research findings coincide with the literature.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…It is stated that providing this atmosphere will increase their loyalty to the company and they will adapt to changing conditions more easily (Bieleń and Kubiczek, 2020). In the study conducted to reveal the ideal manager profile of Generation Z, it is suggested by young people that being like a friend, who will protect and look after them, is important for the leader to be a reliable manager (Aydoğdu and Kara Özkan, 2021). Our research findings coincide with the literature.…”
Section: Discussionsupporting
confidence: 85%
“…Incorporating employees into decision-making processes, resolving conflicts and maintaining the comfort of the working environment becomes possible if the leader is supportive in organizations (Dayanti et al, 2022). According to Generation Z, one of the significant qualities that an ideal leader should possess is that he supports, trusts and respects his employees (Aydoğdu and Kara Özkan, 2021;Gabrielova and Buchko, 2021). According to the results of the study, participants are realized to define providing support as one of the basic duties of a leader.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations